Application of Metathesis Reactions in the Synthesis and Transformations of Functionalized β-Amino Acid Derivatives - Kiss, Loránd; Kardos, Márton; Vass, Csaba; Fülöp, Ferenc (Synthesis, 2018)
Because of their biological relevance, cyclic β-amino acids have generated increasing interest and had significant impact in drug research over the past two decades. Their preparation and further functionalization towards new types of molecular entities have received large interest in synthetic and medicinal chemistry. Various types of metathesis reactions, such as ring-opening (ROM), ring-closing (RCM), or cross metathesis (CM) are used widely for access to either alicyclic β-amino acids or other densely functionalized derivatives of this group of compounds. This account intends to provide an insight into the most relevant synthetic routes to this class of derivatives with the application of metathesis reactions. The review focuses on the presentation of selective and stereocontrolled methodologies in view of versatility, robustness, limitations and efficiency.1 Introduction2 Synthesis and Transformation of Cyclic β-Amino Acids through Metathesis Reactions2.1 Synthesis of Five- and Six-Membered Cyclic β-Amino Acids by Ring-Closing Metathesis2.2 Synthesis of Five- and Six-Membered Cyclic β-Amino Acids by Cross Metathesis2.3 Synthesis of β-Amino Acids with Larger Ring Systems by Ring- Closing Metathesis2.4 Synthesis of β-Amino Acids with Condensed Ring Systems by Ring-Rearrangement Metathesis2.5 Stereocontrolled One-Step Synthesis of Functionalized Cispentacin and Transpentacin Derivatives2.5.1 Stereocontrolled Synthesis of Functionalized Cispentacin and Transpentacin Derivatives through Ring-Opening Metathesis of Norbornene β-Amino Acid Derivatives2.5.2 Stereocontrolled Synthesis of Functionalized Azetidinones and β-Amino Acid Derivatives from Condensed Ring β-Lactams by Ring-Opening Metathesis2.5.3 Carbon–Carbon Double Bond Functionalization of β-Amino Acid Derivatives and β-Lactams with α,β-Unsaturated Carbonyl Compounds through Cross Metathesis2.5.4 Synthesis of Functionalized β-Amino Acid Derivatives and β-Lactams through Chemoselective Cross Metathesis3 Conclusions and Outlook
Keywords: amino acids; heterocycles; metathesis; ring closure; stereoselectivity